A scanning and transmission electron microscopy study of jaagsiekte lesions - Payne, A L; Verwoerd, D W (Onderstepoort journal of veterinary research, 1984)
A scanning electron microscopy (SEM) and transmission electron microscopy (TEM) study was made of lesions from acute, experimentally induced cases of jaagsiekte. In the SEM study tumour cells were easily identified by the abundant microvilli on their peripheral surface. The SEM study gave further insight into the development of lesions and the spatial relationship of cells involved in jaagsiekte. TEM revealed that the tumour cells were in a state of rapid protein synthesis and had many characteristics in common with other malignant cells.